Azolla: The super plant for sustainable feed production - Mooventhan, P; Kumar, Jagdish; Dixit, Anil; Sharma, K C; Sivalingam, P N; Gupta, Amit Kumar; Singh, Uttam; Singh, S R K; Venkatesan, P; Kaushal, Pankaj (Indian Farming, 2019)
Low-cost azolla cultivation under the Farmer FIRST Programme in the tribal areas of Kasdol block in Chhattisgarh has proved to be a successful model in the villages. More than 37 azolla production units were set up in the backyard of the beneficiaries. Around one kg of azolla was harvested within 10 to 15 days of inoculation. Azolla serves as an excellent alternative feed and hence saves around 20% of the poultry feed of the poor farmers in the region.